Simulation Model of Hydrogen Fueled SI Engine - Navale, S. J.; Kulkarni, R. R.; Thipse, S. S. (Penerbit Universiti Malaysia Pahang, 2015)
Limited reserves of fossil fuels and strict pollution norms have forced research towards searching alternate fuels. Hydrogen has great potential as an alternative fuel for Internal Combustion Engine. Understanding behavior of hydrogen fueled spark ignition engine and parameters controlling the performance is important. Simulation is an affordable solution as it saves time and money. In this paper, a mathematical model has been developed. The results acquired from the model and experimental results from literature have shown reasonable agreement. This model was used as a simulation tool for predicting performance of hydrogen fueled SI Engine under variable operating parameters. Finally, engine performances under variable compression ratio have presented.